ENHANCING ESL GRAMMAR TEACHING EFFECTIVENESS THROUGH AUGMENTED REALITY TEACHER TRAINING MODULES - Juraeva Iroda; Xayrullayeva Sugdiyona (Web of Journals Publishing, 2025)
This study examines the implementation of augmented reality (AR) technology in English as a second language grammar teacher training program to improve teaching effectiveness. The study followed 120 ESL teachers from 15 institutions over a 12-month period, comparing traditional teaching methods with AR modules. Results show that AR-trained teachers achieved 43% higher student engagement and 38% improvement in grammar comprehension scores compared to traditionally trained teachers. AR modules include interactive 3D visualizations, real-time feedback systems, and immersive classroom simulations. Statistical analysis shows a significant correlation between exposure to AR sessions and improved pedagogical confidence (r = 0.76, p<0.001). These findings identify AR technology as a transformative tool for professional development in second language education and suggest scalable solutions for global ESL teacher training programs.
Keywords: Augmented reality, ESL teacher training, grammar instruction, educational technology, second language pedagogy, professional development.